Viragens humanitaristas para o desenvolvimento: o caso dos refugiados angolanos no Congo-Léopoldville, 1961-1975 - Ana Guardião (Ler História)
The troubled process of expanding the international refugee assistance and protection system to Africa was guided by a growing investment for the integration of refugees through various development models, especially from the 1960s onwards. This article analyses these shifts focusing on the case of the Angolan refugees in Congo-Léopoldville. It explores the ways in which the United Nations High Commissioner for Refugees (UNHCR) has adapted to the multiple challenges associated with expanding its scope of action. From the construction of new partnerships to the accommodation of resistance on the part of refugees, these adaptation processes demonstrate the transversality of the developmental impetus to late colonial and international models, but also the impacts of the internationalization of human rights and the condemnation of colonialism. This article is part of the special theme section on International Organizations in the Era of Decolonization, guest-edited by José Pedro Monteiro.